Generating Hydrogen Gas with a Polyvinyl Alcohol Membrane Dry Cell Electrolyzer Using KOH Electrolyte - Rohman, Abdul; Rusdianasari; Syarif, Aida (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Global environmental concerns requiring excellent air quality have prompted the development of a variety of eco-friendly energy sources. Hydrogen gas is an environmentally friendly option that may be created using an electrolysis device that converts water into hydrogen (H2) and oxygen (O2). In this study, a dry cell electrolyzer with a polyvinyl alcohol (PVA) membrane was used as a separator between two stainless steel 316 electrodes to generate a high hydrogen yield. The hydrogen gas production from the dry cell electrolyzer was determined using gas chromatography. The results showed that using a KOH electrolyte and a PVA membrane considerably enhanced the hydrogen gas composition. Hydrogen gas compositions after electrolysis using a dry cell electrolyzer without a PVA membrane and KOH electrolyte concentrations of 0 M, 0.04 M, 0.07 M, and 0.11 M being 13.70%, 25.10%, 32.50%, and 15.60%, respectively. With a PVA membrane, the hydrogen compositions were 71.50%, 89.10%, 80.50%, and 84.60%, respectively. The results of these experiments show that the most hydrogen gas was produced utilizing a dry cell electrolyzer with a PVA membrane and a 0.04 M KOH electrolyte concentration. When a PVA membrane and a KOH electrolyte are utilized in electrolysis, the hydrogen gas composition improves significantly compared to when either is utilized.